Bitcoin between concept privacy and issuance mechanism - hashem Majeed , Huda; Odeh Ghanem, Prof. Dr. Ussef (Basra studies journal, 2023)
Bitcoin is an advanced type of electronic money that was invented by unknown parties in 2008.It is based in the virtual world and is based on the pillars of cryptography, as it is an encrypted electronic currency that is traded between two electronic devices using (peer-to-peer) technology, that is, ciphers are traded between two parties, one of which knows the other by symbols only.That is , it is not required to disclose the real identities of users, and it has the characteristics that distinguish it from traditional currencies, represented by its great speed, reducing the cost of remittances, and dispensing with the role of the conventional mediator in traditional banking operations. Its scarcity due to the difficulty of obtaining it, as the number of bitcoins does not exceed million units)21 which is fragmented into small units called ( Satoshi and each bitcoin is one hundred thousand Satoshi Bitcoin is based on a technology called block chains , and this technology receives transactions in the form of blocks and places each block in which the encryption system is completed in the form of a contract in a chain. and you get Bitcoin is according to complex and expensive operations, as it is mined by a process called mining, a process similar to the search for gold and precious metals, and it is carried out by parties that have great experience in the field of technology to solve very complex mathematical algorithms , and it is becoming increasingly difficult until you end up obtaining a Bitcoin unit , and in the meantime The process consumes high electrical energy equivalent to the consumption of a country. As for the other process that leads to obtaining Bitcoin , it is through purchase by miners or by financial exchanges, and outlaw groups may exploit it because it is a currency that is not officially issued. Dealing with it has been banned in Iraq and Egypt either Germany has recognized it and directive 849/2015.European Union